PERSEPSI KONSUMEN TERHADAP BAURAN PEMASARAN KERIPIK CABE HJ.KARMI DI KOTA DUMAI - Susila Pitri; Jum'atri Yusri; Fanny Septya (Fakultas Pertanian, Universitas Riau, 2023)
Business competition in chilli chips in Dumai City had a major impact on the UMKM Hj.Karmi Chili Chips, which experienced a decline in production due to decreased consumer demand. The large number of chili chip businesses in Dumai City require every business, especially Hj.karmi Chili Chips, to formulate the right marketing strategy in order to remain competitive in the target market, one of which is through a marketing mix strategy. This study aims to determine consumer perceptions of the marketing mix (product, price, place, promotion, people, process, and physical evidence) of Hj.Karmi Chili Chips in Dumai City. This study used a survey method in the form of observations and interviews. Sampling using non-probability sampling method on accidental sampling with a sample of 40 respondents. The data analysis method uses descriptive analysis by describing consumer ratings from the Likert scale results. The results showed that overall, the seven elements of the marketing mix of Hj.Karmi Chilli Chips were rated as good by consumers. Price is the element that gets the highest rating score of 4.38 with very good criteria. While promotion is the element that gets the lowest rating score of 3.09 with good enough criteria. Based on the results obtained, it was concluded that Hj.Karmi Chili Chips had advantages in price, people, and process, and had weaknesses in promotion and physical evidence. So it is suggested for Hj.Karmi Chili Chips to improve the marketing mix strategy, especially in the promotion system and physical evidence or sales outlets.